Consistency of science achievement across science subjects among Chinese students and schools. (March 2018) - Ma, Xin; Fan, Meng; Luo, Xingkai
Highlights: Chinese students were highly consistent in achievement across science subjects. Consistency among students did not depend on student and school variables. Chinese schools were extremely consistent in achievement across science subjects. Consistency among schools did not depend on student and school variables. Abstract: A multivariate multilevel model was developed for secondary data analysis of 110, 520 eighth grade students from 592 middle schools in China to examine the educational issue of consistency in science achievement across different science subjects among Chinese students and schools. Results indicated that Chinese students were highly consistent in science achievement across science subjects and this consistency did not depend on student and school characteristics. Meanwhile, Chinese schools were extremely consistent in science achievement across science subjects and this consistency did not depend on student and school characteristics.